Internalization Values Of Character Education Towards The Teruna-Daha In The Medi-Median Tradition - Akio Hiroyuki; I Nengah Juliawan; I Ketut Sudarsana (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2018)
National culture and character education is a concept of character education in Indonesia, namely through the process of internalization of education based on the principles of religious, social and cultural norms. The medi-median tradition is one of the cleansing ceremonies that returns all elements in Bhuana Agung and Bhuana alit back to its place, which is carried out by Krama desa in the traditional village of Tenganan Pegringsingan, which in this tradition gives deep meaning as an internalization of values that form the character of religious young people.  General objectives and specific objectives to examine and analyze medi-median traditions, related to the internalization of the value of character education. This type of qualitative research used religious theory, internalization theory, value theory, and ethnographic research approaches. Accumulation data used observation method, interview method, library method, data that has been collected is analyzed by interpretative descriptive analysis method, analysis conducted during and after accumulation data, data reduction activities, data presentation, verification to make conclusions. The results presentation technique is presented by the method of presenting the data formally and informally. Research results (1) The medi-median tradition is carried out at Sasih Kapitu, with a series of muhu-muhu ceremonies in the dalem kangin and medi-median in the north to south of the village area, with implementation plans initiated by the medimedian initiator. (2) Internalization of character values through 3 stages, namely the value transformation stage, transaction value stage and transinternalisation stage. (3) internalization of character values towards the teruna-daha in the medi-median tradition, which are: religious values, social values, values. tolerance, discipline value, friendly/communicative value, creative value, aesthetic value, and value of responsibility.